Transformative partnerships for a food-secure world (September 2013) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Learning together transforms agriculture and lives. A new version of the video narrated by food policy leader Lindiwe Majele Sibanda. For more information visit: https://ccafs.cgiar.org/research-highlight/farmers-and-scientists-better-together-fight-against-climate-change Watch the original version at: http://youtu.be/5pKaoD5sGjw